Pembelajaran Bahasa Arab Dalam Buku Ta’lim Al-‘Arabiyah Bi Thoriqoh Haditsah M. Fethullah Gülen - Sholihah, Amaliya; Hidayah, Ihadatul (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2020)
The focus of this study is to investigate the thinking of Islamic education figures who have an interest in learning Arabic. This study focuses on a work entitled "Ta'lim Al-" Arabiyyah Bi Tariqah Haditsah ". The significance of this study is how the design made by Gülen in his book for learning Arabic and are there implication and integration of his thinking with learning Arabic. Seeing that Gülen is an Islamic education figure who concerns education including Arabic learning. The method of this study is library research, in which the source of the data is taken from several kinds of literature. The approach of this study is the philosophical analysis-thinking of the figure. Gülen’s framework is a form of his concern in the world of education one of which was towards learning Arabic. Gülen designs the Arabic language learning model in a learning book called Ta’lim Al- “Arabiyyah Bi Tariqah Haditsah which contains a (modern) hadith model design. In his book, Gülen divides Arabic language learning into three levels, beginner, intermediate, and advanced.